Parents Apprehension Towards Online Learning during the Covid-19 Pandemic - Lomi, Nilamsari; Katemba, Caroline V. (8ISC Proceedings: Covid-19; 8ISC Proceedings: Covid-19, 2022)
The COVID-19 pandemic has disrupted the school system, posing numerous challenges for teachers and parents. The most significant difficulty is that the educational institution is unable to provide face-to-face learning in the classroom. This makes parents concerned about their children’s learning styles and academic performance throughout the pandemic. This study sought to determine whether or not parents are concerned about their children’s online English learning, particularly during the Covid-19 pandemic. Research Questions included (1) Do parents worry if their children cannot get good grades in their English subject due to online learning? (2). Do parents worried that their children will not be able to learn English well like in regular school? (3). Was it easy to manage your Children’s studying at home? This study is a qualitative research design, and the questionnaires were distributed face-to-face to the parents. There were 30 parents of a 5th-grade student of SD Yapmas Masehi Waingapu who participated in this study. According to the study’s findings, 86,7 percent of parents are anxious that their children will not receive a good grade as a result of online learning, and 93,3 percent are concerned that their children would not be able to learn English as well would in a regular classroom. The parents also have a difficult time managing their children to study every day. Keywords : parents’ anxiety, homeschooling, zoom, primary education